Spectroscopic Investigations of Interactions of Heteropolyacids with a-Lactalbumin Complexes - F. BAMOHARRAM, FATEMEH; CHAMANI, JAMSHID; M. HERAVI, MAJID; RAJABI, OMID; ROSHANI, MINA; KARIMI, NASRIN; M. HERAVI, OMID (Asian Journal of Chemistry, 2010)
The interaction between a-lactalbumin with heteropoly acids occurred. The best denaturation of a-lactalbumin with Preyssler heteropoly acid occured in comparison with heteropoly acids including Keggin and Dawson structures. Based on calculated thermodynamics parameteres, it is shown that during denaturation of protein, preyssler heteropoly acid has the highest ΔG(H2O), m value and lowest Cm at the shortest time compared with other polyoxometalates (POMs) with Keggin and Dawson structures. The electrostatic interaction of protein with various heteropoly acids is important on a molecular level for the interpretation and development of model compounds with selective affinity for particular proteins.